Narracje alternatywne i marginalne w uchwałach rocznicowych Sejmu i Senatu Rzeczypospolitej Polskiej w latach 2009-2019. Przykład uchwał upamiętniających 70. i 80. rocznicę wybuchu II wojny światowej - Secler, Bartłomiej (My University, 2021)
"Alternative and Marginal Narrations in the Anniversary Resolutions of the Sejm and Senate of the Republic of Poland in 2009-2019. Example of Resolutions Commemorating the 70th and 80th Anniversaries of the Outbreak of the Second World War". Historical anniversaries generate breakthroughs, mark systemic and political turns, and remind us of the events and characters from the past. The subject of the article are the anniversary resolutions of the Sejm and the Senate of the Republic of Poland, which I define as a tool for shaping the politics of memory and collective memory that are one of the forms of commemorating the past and serving the political authorities as means for its interpretation. I assume that the choice of anniversaries and historical figures that deserve to be commemorated is dictated by the ideological and political orientation of political parties and groups. In the above context, it is worth asking the question – referring to the title of the article – should the anniversary resolutions of the Sejm and the Senate of the Republic of Poland, their form, content, as well as way of proceeding and adopting them be considered as important and momentous narratives, or rather as alternative and marginal ones? The considerations will be illustrated with examples of resolutions adopted on the occasion of the 70th and 80th anniversaries of the outbreak of the Second World War.
Keywords: uchwała rocznicowa; polityka pamięci; postpamięć; pamięć zbiorowa; II wojna światowa; upamiętnienie